Effect of Chemical Treatment on Physical, Mechanical and Thermal Properties of Ladies Finger Natural Fiber. (1st October 2013) - Hossain, S. I.; Hasan, M.; Hasan, Md. N.; Hassan, A.
Abstract : In present research, natural fiber obtained from ladies finger plant was chemically treated separately using alkali (2% NaOH), chromium sulfate (4% Cr 2 ( SO 4 ) 3 12 ( H 2 O ) ), and chromium sulfate and sodium bicarbonate (4% Cr 2 ( SO 4 ) 3 12 ( H 2 O ) + NaHCO 3 ). Both raw and chemically treated fibers were subsequently characterized using mechanical (tensile), structural (Fourier transform infrared spectroscopy and scanning electron microscopy), and thermal (thermogravimetric) analysis. Fourier analysis showed the presence of (−OH) group in the ladies plant fiber. Scanning electron micrographs revealed rougher surface in case of alkali treated fiber, while thin coating layer was formed on the fiber surface during other two treatments. Tensile test on ladies finger single fiber was carried out by varying span length. The tensile strength and Young's modulus values were found to be increased after chemical treatment. For both raw and chemically treated fibers, Young's modulus increased and tensile strength decreased with increase in span length. Thermogravimetric analysis indicated the same level of thermal stability for both raw and treated ladies finger fibers.